Development of quantum dot-phthalocyanine integrated G-quadruplex/double-stranded DNA biosensor - Topcu, Ayse; Bagda, Esra; Oymak, Tulay; Durmuş, Mahmut (Academic Press Inc Elsevier Science, 2022)
In the present study, the phthalocyanine (Pc) integrated mercaptopropionic acid capped quantum dot (mpa@QD) biosensor has been developed for the quantitative determination of G-quadruplex and double -stranded DNA. The working principle of the developed biosensor platform is based on the quenching of the emission signal of the mpa@QD in the presence of Pc (closed position) and the recovery of the fluorescence signal in the presence of DNA (open position). The parameters affecting biosensor performance, such as Pc type and concentration, were optimized. Since the developed biosensor aimed to determine G-quadruplex and double -stranded DNA in biological samples, the effect of common ions (such as Na+, Mg2+) and serum albumin found in many biological matrices on the biosensor performance were examined. The effect of common ions on biosensor signal was negligible, except Zn2+. The analytical properties of the biosensor, such as linear range, calibration sensitivity, relative standard deviation %, the limit of detection, and quantification, were determined. The limit of detection and quantification values were found 0.055 mu M and 0.18 mu M for AS1411, 0.061 mu M and 0.20 mu M for Tel21, 0.038 mu M and 0.13 mu M for Tel45 and 0.091 mu M and 0.30 mu M for ctDNA. Several different synthetic samples were prepared. The spiked synthetic samples such as mammalian cell medium were used to evaluate the analytical performance of Pc-mpa@QD. All synthetic samples were prepared with polyethylene glycol, which resembles biological samples' crowded environment.
Keywords: G-quadruplex; Quantum dot; Phthalocyanine; Biosensor